A robust and semi-automatic procedure for Silicon Photomultipliers characterisation. (8th March 2017) - Arosio, V.; Beretta, M.; Caccia, M.; Santoro, R.
Abstract: Silicon Photomultipliers are state-of-the-art solid state sensors of light with single photon sensitivity, unprecedented photon number resolving capability and high photon detection efficiency. SiPM are cost effective, compact, magnetic field insensitive and with an extreme flexibility in the design to cope with different applications in fundamental and applied science and industry. As a rapidly evolving technology, new generation of sensors are being continuously proposed by different producers, requiring the development of reliable and efficient SiPM characterisation methods to perform a quick assessment and comparison. The procedure presented here is based on post-processing of digitised SiPM waveforms recording the response of the sensor to an ultra-fast light pulse. For every pulse, the signal is synchronously sampled, digitised and recorded on the timescale of a few microseconds with the objective of extracting from a single set of waveforms a full picture of the sensor characteristics in terms of Gain, Breakdown Voltage, Dark Count Rate, Optical Cross-Talk and After Pulse probability. The need of a unique and consistent data-set guarantees a fast and robust characterisation, stable against environmental condition changes, notably temperature.